Impacto da esplenectomia associada à vagotomia sobre o conteúdo de tecido adiposo e o controle secretor de insulina em ratos wistar - Siqueira, Bruna Schumaker (2019)
The vagus nerve (VN) exerts important effects on glucose-induced insulin secretion (GIIS) and on metabolism, an event that may involve splenic activity. In this work, we evaluated the effect of vagotomy (VAG) associated or not to splenectomy (SPL) on the metabolism and insulin secretion of male Wistar rats. At 60 days the rats were submitted to VAG, SPL, VAG+SPL or false operated (SHAM) surgeries (n =17 rats /group). At 149 days, they were submitted to glucose tolerance test. Body weight, dietary intake, weight of fat deposits, and biochemical parameters from the collection of blood plasma were assessed and evaluated. In addition, pancreatic islets were isolated to evaluate GIIS, autonomic responses and expression of muscarinic receptor subtype 3 (mAchR3) and protein kinase c (PKCα), we performed the histological analysis of the pancreas and also recorded VN neural activity. Anova two-way analysis, with Tukey posttest (p <0.05). VAG led to reduction in body weight, increased consumption, implying lower feed efficiency. Reduced deposits of white adipose tissue, an effect that was attenuated in the VAG+SPL group. SPL reduced blood glucose and improved HOMA index without altering glucose tolerance, and VAG decreased triglycerides, improving TyG, in contrast to increased cholesterol levels. The GIIS was reduced in the VAG+SPL group. In the presence of a cholinergic agonist, SPL potentiated the inhibitory effect of VAG, further reducing GIIS, without altering mACHR3 expression. Only the VAG altered the expression of PKCα leading to the reduction in protein expression in the VAG and VAG+SPL groups. SPL had effects reducing the neural activity of the vagus in SPL and VAG+SPL animals. In addition, SPL increased the inhibitory effect of oxymetazoline on the reduction of GIIS in the SPL and VAG+SPL groups. In summary, this study showed that SPL can attenuate the lipolytic effect of VAG, without impeding the vagal effects on metabolism, growth and food intake. In addition, VAG associated with SPL reduced GIIS, but only SPL decreased cholinergic effect and VN activity, without altering the expression of mAchR3 or PKCα in isolated pancreatic islets, suggesting the potential role of the spleen in modulating neural flow autonomic.